2017
DOI: 10.1007/s13272-017-0238-3
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to enable automatic 3D routing of aircraft Electrical Wiring Interconnection System

Abstract: Harness 3D routing is one of the most challenging steps in the design of aircraft Electrical Wiring Interconnection System (EWIS). This is due not only to the intrinsic complexity of the EWIS, but also to the increasing number of applying design constraints and its dependency on any change in the design of the airframe and installed systems. The current routing process employed by EWISdesign is largely based on the manual work of expert engineers, partially supported by conventional CAD systems. As a result, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…La Rocca describes a typical KBE application for aircraft applications. This is an applicative case that shows how this technique is efficient in helping the designer to analyze and solve problems that must face frequently (Zhu et al, 2017). One of the hard challenges in the aircraft design is the modelling of the harness 3D routing.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…La Rocca describes a typical KBE application for aircraft applications. This is an applicative case that shows how this technique is efficient in helping the designer to analyze and solve problems that must face frequently (Zhu et al, 2017). One of the hard challenges in the aircraft design is the modelling of the harness 3D routing.…”
Section: State Of the Artmentioning
confidence: 99%
“…The difficulty stays in its intrinsic complexity, but also in the increasing of the design constraints and in its dependency on any little change. Zhu et al (2017) proposed methods based on KBE and optimization to reach minimum cost routing solutions that satisfy constraints of all relevant design rules. In all cases, despite how they are called, during the design phase the designer has to face, consciously or not, a set of rules to solve.…”
Section: State Of the Artmentioning
confidence: 99%
“…A two-steps optimization method was proposed in our previous work to enable automation of the harness routing design. 8,9 In the first step, a 3 D discretization of the airframe surfaces where the EWIS is allowed to be fixed is generated and no-go areas (i.e., where systems are installed) are identified. Then, a simplified harness is routed through the nodes of the discretized surfaces representation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, KBE applications are usually applied to automate design routines avoiding of repetitive tasks (Verhangen et al, 2012). This technology has its roots in Artificial Intelligence (AI) to analyse and solve problems that must face frequently (Zhu, et al, 2017). Despite such tools, it has been observed that many companies just base the process on poor empirical models working by analogy on the basis of the expertise of senior designers and searching for similar past solutions.…”
Section: Introduction and State-of-the-artmentioning
confidence: 99%